Determination of L-Theanine and Caffeine Contents in Tea Infusions with Different Fermentation Degrees and Brewing Conditions Using the Chromatographic Method - Gamze Ayakdaş; Duygu Ağagündüz (Foods)
This study aimed to determine the caffeine and L-theanine contents in tea infusions prepared under varying fermentation degrees, brewing conditions (temperature and time), and serving methods (tea bag/loose-leaf). Infusions of six tea types (green, white, yellow, oolong, black, and Pu-erh) and various serving forms of green, white, and black tea were brewed at 80 °C and 100 °C for 2, 5, and 10 min. Contents were analyzed using reversed-phase high-performance liquid chromatography. Caffeine levels were highest in black and yellow tea (14 ± 1.0 mg/200 mL and 13.8 ± 0.2 mg/200 mL, respectively), both of which were significantly higher than the levels in green, white, and oolong tea (11 ± 2.1 mg/200 mL; 5.8 ± 0.7 mg/200 mL; and 4 ± 1.6 mg/200 mL, respectively; p < 0.001), whereas Pu-erh tea (13 ± 2.9 mg/200 mL) had caffeine levels comparable to that of black tea (p > 0.05). L-Theanine levels were highest in black and green tea (12.3 ± 2.8 mg/200 mL and 12.5 ± 2.5 mg/200 mL, respectively), and these levels were significantly higher than those in the other tea types (p < 0.001). Brewing temperature only affected caffeine levels n, whereas L-oolong tea (4.4 → 13.5 mg/200 mL, p < 0.05); theanine remained stable (p > 0.05). Longer brewing times significantly raised both components (e.g., yellow tea caffeine levels rose to 53 ± 16.9 mg/200 mL at 10 min; p < 0.05). In black tea, cup-sized bags yielded higher caffeine levels (39 ± 9.9 mg/200 mL) than loose-leaf (24 ± 7.2 mg/200 mL) and teapot bags (p < 0.001). Serving method had no effect on green and white teas (p > 0.05). In conclusion, fermentation rate, brewing conditions, and serving method were found to influence the caffeine and L-theanine levels of tea infusions.